2008
DOI: 10.1007/s10800-008-9711-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cathodic potential on the local electrochemical environment under a disbonded coating

Abstract: A rectangular crevice assembly was used to investigate the effects of cathodic protection (CP) potential, bubbling CO 2 and surface condition on the crevice corrosion of X70 steel under a disbonded coating. The solution within the crevice becomes more alkaline due to the reduction of dissolved O 2 . As a result, the potential of the steel reaches the protected potential range and thus the protection distance becomes longer when the applied CP potential is more negative. Potential drop (IR) mainly occurs in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…Over the past decades, many attempts have been made to develop various testing and inspection techniques and experimental devices for investigating CUDC in the laboratory. Common approaches include the simulation of corrosion using artificial coating disbondment devices under the influence of disbondment crevice geometry by measuring the potential gradient [12,13,[21][22][23][24][25][26][27][28][29][30], pH distribution [12,13,[21][22][23][24][25][26][27][28][29][30], current profile [21,24,29,30] and oxygen concentration [12,13,22,23,27] within the crevices of disbonded coatings in aqueous solutions. These experiments have gained valuable data and understanding of CUDC; however an issue with most CUDC testing and inspection techniques is that they generally do not have both high temporal and spatial resolutions required for investigating complex and dynamic CUDC processes, mechanisms and influence factors.…”
Section: Laboratory Probing Of Cudcmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decades, many attempts have been made to develop various testing and inspection techniques and experimental devices for investigating CUDC in the laboratory. Common approaches include the simulation of corrosion using artificial coating disbondment devices under the influence of disbondment crevice geometry by measuring the potential gradient [12,13,[21][22][23][24][25][26][27][28][29][30], pH distribution [12,13,[21][22][23][24][25][26][27][28][29][30], current profile [21,24,29,30] and oxygen concentration [12,13,22,23,27] within the crevices of disbonded coatings in aqueous solutions. These experiments have gained valuable data and understanding of CUDC; however an issue with most CUDC testing and inspection techniques is that they generally do not have both high temporal and spatial resolutions required for investigating complex and dynamic CUDC processes, mechanisms and influence factors.…”
Section: Laboratory Probing Of Cudcmentioning
confidence: 99%
“…Figure 1 illustrates corrosion occurring within the crevice between the metal surface and the disbonded coating layer. The crevice provides easy lateral paths for corrosive species to reach the metal surface while simultaneously shielding cathodic protection currents from reaching the metal substrate, permitting the initiation and propagation of many types of corrosion [5][6][7][8][9][10][11] including pitting [12], microbiologically induced corrosion (MIC) [13,14] and stress corrosion cracking (SCC) [15,16]. Currently, CUDC remains as major failure mode, probably the worst-case scenario form of electrochemical corrosion, affecting the integrity of civil and industrial infrastructures such as buried and submerged pipelines [3].…”
Section: Introductionmentioning
confidence: 99%
“…Jack et al have found that the pH increases from 7.20 to 7.49 in the crevice after polarizing for 1 month . The results of Chen et al have shown that the pH increases with time in the absence of the applied potential and reaches above 8.0 at the distance of 25 cm away from the holiday . Lara and Klechka have found that the pH has a relation with the applied potential in the crevice, and the pH value reaches 11 at the applied potential of −950 mV vsCSE .…”
Section: Introductionmentioning
confidence: 99%
“…16 The results of Chen et al have shown that the pH increases with time in the absence of the applied potential and reaches above 8.0 at the distance of 25 cm away from the holiday. 17 Lara and Klechka have found that the pH has a relation with the applied potential in the crevice, and the pH value reaches 11 at the applied potential of −950 mV vsCSE . 18 The studies by Perdomo and Song have shown that the concentrations of the dissolved oxygen decrease with time.…”
Section: Introductionmentioning
confidence: 99%
“…Many laboratory, field, and theoretical studies have been performed to design a suitable protection system [6][7][8][9][10][11][12][13][14][15][16]. These studies have mainly focused on the distribution of the electrical potential and current within the crevices, the mass transfer process, the mechanism of crevice corrosion, and the mathematical modeling of the phenomenon of cathodic protection.…”
Section: Introductionmentioning
confidence: 99%